Avaliação do gerenciamento e disposição final dos resíduos químicos de laboratórios do IGCE, UNESP - Rio Claro/SP - Lise, Renato Boarin [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Laboratory of Chemical Waste Management programs are being implemented in various universities of the country and the world, in recognition of the urgent need to change the reality of disregard for the environment, together with objective responsibility of the generator, and especially the awareness of sustainability. Analysis and research laboratories involve a range of waste in developing their studies with intrinsic characteristics related to their form of generation. The amount of waste generated in this segment is negligible compared to industrial activities, but the environmental issue is that these residues do not have a standard technique for treatment due to the potential variation of its composition. This research project, aiming their suitability and continuous improvement, aims to diagnose and analyze the current situation of the management and disposal of chemical waste generated by the laboratories IGCE UNESP, Campus Rio Claro / SP. Universities, through their research, teaching and extension, end up generating potentially hazardous chemicals that may contaminate the environment when they are disposed of improperly, with no concern for the environment and / or public health. Aiming to assist in improvements with respect to this issue, the purpose of this study is to understand the management and disposal of chemical waste from the IGCE, laboratories UNESP - Rio Claro / SP, in order to discuss the situation of such waste, and present proposals to reduce generation of the same and minimizing the environmental impact, thereby increasing the local hygiene through proper disposal. The research instrument used interviews, questionnaires, review of recent literature and observations were made in order to develop proposals for the management and disposal of waste. These proposals based on prevention and corrective control, where the preventive approach aims at lifting techniques and actions to reduce the generating sources and...

Programas de Gerenciamento de Resíduos Químicos Laboratoriais vêm sendo implantados em várias universidades do país e do mundo, em reconhecimento à necessidade urgente de alterar a realidade de descaso para com o ambiente, associado à responsabilidade objetiva do gerador e, principalmente, à consciência de sustentabilidade. Laboratórios de análises e pesquisas envolvem uma gama de resíduos no desenvolvimento de seus estudos com características intrínsecas referentes à sua forma de geração. A quantidade gerada de resíduos neste segmento é desprezível comparado às atividades industriais, mas a questão ambiental é que estes resíduos não possuem uma técnica padrão para o seu tratamento, devido ao potencial de variação da sua composição. O presente projeto de pesquisa, visando sua adequação e melhoria contínua, tem como objetivo diagnosticar e analisar a situação atual do gerenciamento e disposição final dos resíduos químicos gerados pelos laboratórios do IGCE da UNESP, campus Rio Claro/SP. As universidades, através das suas atividades de pesquisa, ensino e extensão, acabam gerando resíduos químicos potencialmente perigosos que podem vir a contaminar o ambiente no momento em que são descartados de maneira incorreta, sem nenhuma preocupação com o ambiente e/ou saúde pública. Visando auxiliar nas melhorias com relação a esse problema, a proposta desse trabalho é compreender o gerenciamento e disposição final dos resíduos químicos dos laboratórios do IGCE, UNESP - Rio Claro/SP, de maneira a discutir a situação desses resíduos e apresentar propostas para reduzir a geração dos mesmos e minimizar o impacto ambiental, aumentando assim a higiene local através da disposição final adequada. Como instrumento de pesquisa foram feitas entrevistas, aplicação de questionário, revisão da literatura recente e observações a fim de se elaborar propostas para o gerenciamento e disposição dos...
Keywords: Universidade Estadual Paulista Júlio de Mesquita Filho Instituto de Geociencias e Ciencias Exatas; Resíduos; Gerenciamento de resíduos; Laboratorios; Impacto ambiental; Rio Claro (SP)